Petiole phosphorus, magnesium and sulphur concentrations are controlled by rootstocks with Vitis riparia genetic background in grapevine - Elisa Marguerit (OENO One, 2020)
Backgrounds and aims: Grapevine, Vitis vinifera, requires grafting on Phylloxera tolerant rootstocks of American origin in most viticultural areas of the world. The most commonly used species in rootstock creation are V. berlandieri, V. riparia and V. rupestris. Rootstocks not only provide tolerance to Phylloxera but assure the supply of water and mineral nutrients to the scion. The objective of this work was to determine to what extent rootstocks of different genetic backgrounds alter the mineral composition of petioles of grapevine.